Asymmetric transmission and optical low-pass filtering in a stack of random media with graded transport mean free path - Jayachandra, Bangi (2016)
Light transport and the physical phenomena related to light propagation in random media are very intriguing, they also provide scope for new paradigms of device functionality, most of which remain unexplored. Here we demonstrate, experimentally and by simulation, a novel kind of asymmetric light transmission (diffusion) in a stack of random media (SRM) with graded transport mean free path. The structure is studied in terms of transmission, of photons propagated through and photons generated within the SRM. It is observed that the SRM exhibits asymmetric transmission property with a transmission contrast of 0.25. In addition, it is shown that the SRM works as a perfect optical low-pass filter with a well-defined cutoff wavelength at 580 nm. Further, the photons generated within the SRM found to exhibit functionality similar to an optical diode with a transmission contrast of 0.62. The basis of this functionality is explained in terms of wavelength dependent photon randomization and the graded transport mean free path of SRM.